2019
DOI: 10.5603/gp.a2019.0045
|View full text |Cite
|
Sign up to set email alerts
|

The expression of Platelet-derived Growth factor receptors (PDGFRs) and their correlation with overall survival of patients with ovarian cancer

Abstract: Objectives:The main aim of the study was to investigate the expression of Platelet-Derived Growth Factor Receptors alpha (PDGFR-alpha) and beta (PDGFR-beta) in malignant and benign ovarian tumors. We performed an analysis of the correlation of PDGFRs expression and stage of the disease, tumor grade and histopathological type of epithelial ovarian cancer (EOC). Additionally, we evaluated patient prognosis according to PDGFR expression. Material and methods:Our study group was composed of 52 samples of EOCs, 35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…These analyses could help to find some miRNAs, TFs and hub genes involved in the regulation of endometriosis. CCND2 [246], VCAM1 [190], PDGFB (platelet derived growth factor subunit B) [221], PTCH1 [263], FOXQ1 [210], IGF2BP1 [324], ACTC1 [359], EPB41L3 [315], DAPK1 [379], hsa-mir-17-5p [1663], TCF3 [1664], RNF2 [1665], CLOCK (clock circadian regulator) [1666], SMARCA4 [1667] and TRIM28 [1668] provided a clear picture of the prognosis of patients with ovarian cancer. CCND2 [511], VCAM1 [478], PTCH1 [523], FOXQ1 [492], IGF2BP1 [568], EPB41L3 [560], DAPK1 [609], hsa-mir-17-5p [1669], TCF3 [1670] and TRIM28 [1671] as a biomarkers for cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These analyses could help to find some miRNAs, TFs and hub genes involved in the regulation of endometriosis. CCND2 [246], VCAM1 [190], PDGFB (platelet derived growth factor subunit B) [221], PTCH1 [263], FOXQ1 [210], IGF2BP1 [324], ACTC1 [359], EPB41L3 [315], DAPK1 [379], hsa-mir-17-5p [1663], TCF3 [1664], RNF2 [1665], CLOCK (clock circadian regulator) [1666], SMARCA4 [1667] and TRIM28 [1668] provided a clear picture of the prognosis of patients with ovarian cancer. CCND2 [511], VCAM1 [478], PTCH1 [523], FOXQ1 [492], IGF2BP1 [568], EPB41L3 [560], DAPK1 [609], hsa-mir-17-5p [1669], TCF3 [1670] and TRIM28 [1671] as a biomarkers for cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…FOXQ1 [210], WNT5A [211], MEOX1 [212], DOCK4 [213], TIMP3 [214], ADAMTS9 [215], NDNF (neuron derived neurotrophic factor) [216], NETO1 [217], CD24 [218], LHCGR (luteinizing hormone/choriogonadotropin receptor) [219], SCD (stearoyl-CoA desaturase) [220], PDGFB (platelet derived growth factor subunit B) [221], MMRN1 [222], LDLR (low density lipoprotein receptor) [223], CD4 [224], FOXL2 [225], TRPA1 [226], EPHA5 [227], TOX (thymocyte selection associated high mobility group box) [228] [253], CLDN3 [254], LEPR (leptin receptor) [255], IL15 [256], BMP2 [257], LAMA5 [258], NTNG1 [259], KRT19 [260], ROS1 [261], APOE (apolipoprotein E) [262], PTCH1 [263], ITPKA (inositol-trisphosphate 3-kinase A) [264], CASP1 [265], NID1 [266], ABCG2 [267], ACE (angiotensin I converting enzyme) [268], PGR (progesterone receptor) [269], WLS (Wnt ligand secretion mediator) [270], KLK3 [271], LRP1B [272], LY6K [273], ALPP (alkaline phosphatase, placental) [274], PRAME (PRAME nuclear receptor transcriptional regulator) [275], SLCO4A1 [276], EGFL6…”
Section: Go and Pathway Enrichment Analyses Of Degsmentioning
confidence: 99%
“…Tumor angiogenesis is closely related to platelets. 38 Platelets come into contact with prethrombus structures such as collagen in blood vessels, causing changes in blood flow, and endothelial cells release von Willebrand factor to activate platelets. Activated platelets mainly release regulatory factors that promote angiogenesis, such as VEGF and PDGF.…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic development, cell proliferation, survival, differentiation, chemotaxis, and migration are all regulated by the protein that the PDGFRB gene produces [ 35 , 36 ]. Previous studies have established the link between PDGFRB overexpression and a poor prognosis in patients with renal cell carcinoma [ 37 ], oral squamous cell carcinoma [ 38 ], ovarian cancer [ 39 ], and colorectal cancer [ 40 ]. Involved in cell proliferation, the transcriptional activator FOXM1 may have an impact on the expression of several cell cycle genes, including cyclin B1 and cyclin D. Numerous studies have revealed the association of elevated FOXM1 expression levels with a poor prognosis in patients with ovarian cancer [ 41 ], pancreatic and esophageal cancers [ 42 ], malignant rhabdoid tumors [ 41 ], and small-cell lung cancer [ 43 ].…”
Section: Discussionmentioning
confidence: 99%